1908
DOI: 10.1002/path.1700120107
|View full text |Cite
|
Sign up to set email alerts
|

Polyarteritis acuta nodosa and periarteritis nodosa

Abstract: I. INTRODUCTORY. THE term " I'eriarteritis Nodosa " has been applied more or less promiscuously t o two entirely distinct diseases oi the smaller arteries, both of them extremely rare, and both arording problems of considerable interest and difficulty with regard to their histological characters and etiology. One of these conditions is probably a true pemhrteritis, commencing in and affecting chiefly the outer coat of the diseased vessel, though the media and intima may also be affected. For these cases it is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1923
1923
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Ferrari proposed using the term "polyarteritis acuta nodosa" rather than "periarteritis nodosa" because of the transmural rather than perivascular nature of the inflammatory lesions [6], This proposal was convincingly championed by Carnegie Dickson ofthe University of Edinburgh [7]. who published the first extensive account of the disease in the English language literature, although there had been earlier case reports, "Polyarteritis acuta nodosa" has been shortened to "polyarteritis nodosa" (PAN) and is currently the most widely used name for the pattern of arteritis described by Kussmal and Maier,…”
Section: Anca'associated Vasculitismentioning
confidence: 99%
See 1 more Smart Citation
“…Ferrari proposed using the term "polyarteritis acuta nodosa" rather than "periarteritis nodosa" because of the transmural rather than perivascular nature of the inflammatory lesions [6], This proposal was convincingly championed by Carnegie Dickson ofthe University of Edinburgh [7]. who published the first extensive account of the disease in the English language literature, although there had been earlier case reports, "Polyarteritis acuta nodosa" has been shortened to "polyarteritis nodosa" (PAN) and is currently the most widely used name for the pattern of arteritis described by Kussmal and Maier,…”
Section: Anca'associated Vasculitismentioning
confidence: 99%
“…Half the patients are positive for ANCA [6]. Jennette and Falk demonstrated that perinuclear fluorescent staining, which is the pattern usually found, was often due to antibodies directed against myeloperoxidase (MPO) [7].…”
Section: Polyarteritis Nodosa and Microscopic Polyangiitis L Guillevmentioning
confidence: 99%
“…In summarizing the case of a 45-year-old alcoholic man, Ferrari surmises that the vascular lesion is caused by a toxic substance that affects the nerve centers of the vessels (36). W. E. Carnegie Dickson in Edinburgh introduced the term polyarteritis nodosa to the English language literature in 1908 (18). Dickson distinguished "true periarteritis (italics original) commencing in and affecting chiefly the outer coat of the diseased vessel," and adopted the term polyarteritis acuta nodosa, as suggested by Ferrari, for the more rare form of arteritis associated with nodulosis of the small-and medium-sized arteries which are due to " .…”
Section: Nosology Of Polyarteritis Nodosamentioning
confidence: 99%
“…Newly recognized types of this disease were characterized and classified according to features that were similar to or distinct from those of PAN (Klinger, 1931;Churg & Strauss, 1951). In the early 1900s, Ferrari (1903) and Dickson (1908) proposed the name polyarteritis nodosa, partly to distinguish the disorder described by Kussmaul & Maier (1866) from the vascular lesion of tertiary syphilis. Furthermore, the term polyarteritis nodosa emphasizes the panarteritic nature of this disease and underscores the fact that multiple arteries are affected by the process (Arkin, 1930).…”
Section: Polyarteritis Nodosa (Pan)mentioning
confidence: 99%